Enhancing velocity model for gas cloud using first break travel time tomography full waveform inversion - Prajapati, S. (International Petroleum Technology Conference (IPTC), 2019)
The velocity model is of a great importance for geological as well as structural properties of complex structure such as gas cloud. Instead of ray-based techniques, eikonal wavefield tomography can provide a higher resolution velocity model for seismic images. We have implemented first break travel time tomography to enhance the initial velocity model for seismic full waveform inversion (FWI) for better imaging rather than guess initial velocity model for FWI. The First-break travel time concept is based on the eikonal equation, relies on inversion to resolve the complex gas cloud imaging. It allows not only the receivers but the shots to change position along the ray path. Tomography results are useful particularly significant in the presence of noise, scattering in the data. We have implemented this approach on marmousi as well as gas cloud model and output are used as input velocity model for FWI and results of proposed approach is more robust than the traditional with faster convergence. Â© 2019, International Petroleum Technology Conference